Designing a measurement scale for student engagement motivation in higher education - Quynh, Quynh Hai; Nguyen, Hoai Thanh (Jurnal Cakrawala Pendidikan, 2026)
This research aims to present comprehensive literature on student engagement motivation (SEMo) from specific perspectives to develop a scale measuring its domain. This study will first show the context and need for this research in Vietnam, as well as explore the factors and results of previous studies that have been undertaken meticulously. In addition, it provides a definition and aspects of the elements that constitute SEMo in this research context. Finally, to measure these domains, setting up a scale for SEMo is indispensable. As a result, the motivations of consumers to participate in the SEMo were Career orientation, Financial relevance, Self-enhancement, Memorable emotion, and Meaningful behavior. After a scale development procedure, a 30-item instrument representing four domains of a SEMo was shown to be reliable and valid. The study provides a standardized scale for researchers to measure motivation for engagement, facilitating exploration and comparison across different contexts. Additionally, it emphasizes the interaction between students and educational administrators, suggesting potential applications for educational program design in higher education institutions. <!--a=1-->